Chapter Nietzsche e l'immaginazione culturale in Russia all'inizio del XX secolo. Un caso di studio: Dmitrij Merežkovskij - Caprioglio, Nadia (Biblioteca di Studi Slavistici, 2019)
In the decades prior to the Revolution of 1917, the Russian intelligencija was strongly influenced by Western European intellectuals, including Friedrich Nietzsche. Nietzsche was one of the European philosophers who played a prominent role in shaping Russian perceptions of reality in this period, although his thought was interpreted by Russians in contrasing ways. The article examines the case of Dmitrij Merežkovskij, reassessing the extent of Nietzsche's influence on his oeuvre. In our view, Nietzsche did not only influence Merežkovskij's early poetry, where aesthetic and anti-Christian views prevail, but also contributed to the sensual and individualist nature of his later prose.